Identification Study to determine Some Active Substances In Marjoram Plant Extracts - Amel Naji Wadi; Zainab Mahmood Abdulla; Hadi Kareem Dahaam (Journal of Madenat Alelem University College, 2015)
The research contained preparation of Marjoram plant extract in aqueous / alcoholic 50 / 50 (extraction temperature at 65 ˚C). and examination of plant extract by infrared spectroscopy FT-IR and ultra violate spectroscopy UV. The technique of gas chromatography - mass spectrometry GC-Mass for the identification of some of the ingredients of extraction by soxilet, Such as Nitrosomethane ,Hydroxypropanoic acid, di-tert-Butyl dicarbonate, Phthalic acid, Trimethyldecane compounds and flavonoids.